Narrative descriptions in Stephenie Meyer’s Twilight Saga. A corpus stylistics perspective. - Cesiri, Daniela; Coccetta, Francesca (Umanistica Digitale, 2019)
The present study draws on corpus stylistics (cf. Semino, Short 2004; Hoover 2007; Mahlberg 2014; Hoover, Culpeper, O’Halloran 2014, to name a few) to investigate the narrative style in Stephenie Meyer’s The Twilight Saga (2005-2008). In particular, it focuses on keywords generated using Wordsmith Tools version 7 (Scott 2017), and the BNC as reference corpus. Qualitative and quantitative analyses show that the most frequent lexical words (nouns, adjectives, and verbs) reflect the writer’s focus on carefully selected physical elements of the characters. More specifically, the nouns preferentially denote specific physical attributes of the characters, the adjectives provide a general description of the protagonists and the setting, while the verbs used present the actions of all the characters, their interaction with the other protagonists, and their position in the narrative situation.